2, 4, 6‐Trimethylpyridine‐Derived Vinylene‐Linked Covalent Organic Frameworks for Confined Catalytic Esterification. Issue 44 (5th October 2022) - Meng, Fancheng; Bi, Shuai; Sun, Zuobang; Wu, Dongqing; Zhang, Fan
Abstract: Knoevenagel condensation is a powerful tool for the construction of vinylene‐linked covalent organic frameworks. Herein, we established a concise approach to vinylene‐linked COFs by Knoevenagel condensation at the multi‐methyl groups of a pyridine ring through in situ formation of an N ‐acyl pyridinium cation in the presence of various acylating reagents. Following this strategy, two vinylene‐linked COFs were constructed using 2, 4, 6‐trimethylpyridine and multi‐aldehyde‐substituted aromatic derivatives as monomers. The resultant COFs are highly crystalline and assembled into hexagonal lattices with specific surface areas as large as 1915 m 2 g −1 (vs. 1972 m 2 g −1 of the theoretical value). The stable and abundant pyridine‐decorated regular nanochannels within the COFs allow for catalyzing the esterification of several pharmaceutical intermediates with distinct spatially confined selectivity and recyclability, representing an environmentally friendly catalytic organic transformation. Abstract : Knoevenagel condensation at the methyl groups of a 2, 4, 6‐trimethylpyridine monomer was promoted by in situ acylation of the nitrogen atom, yielding highly crystalline vinylene‐linked covalent organic frameworks. The resultant Lewis basic, pyridine‐decorated, regular, nanoporous structures catalyzed spatially confined organic esterification with good selectivity.